Mentoring Roles in Developing Leadership Capacity of Student Teachers in Gambia: Abdou Barrow*, Mahurni, Irkham Zamzuri - Abdou Barrow; Mahurni; Irkham Zamzuri (Samudra Publisher, 2024)
This study aims to understand the mentoring role in developing the leadership capacity of student teachers from the perspectives of the mentor, the mentee, and the head teacher. It explored the opportunities and pitfalls that arise during the mentoring process and how they affect the development of leadership skills in student teachers. Data was collected through Google form questionnaire and telephone interviews with the mentor, mentee (the student teacher), and the head teacher. The findings of this study revealed that mentoring could be a valuable tool for supporting the professional development and leadership capacity of student teachers. However, effective mentoring relationships depend on various factors, including the mentor's qualifications, experience, support of the mentor, the readiness and willingness of the mentee to learn, and the level of support the head teacher provides, some of which are identified as challenges in the study. Thus, effective mentoring programs should be supported by the appropriate training, resources, and support to ensure mentors are equipped to support their mentees in developing their leadership skills. The head teachers should be aware of the importance of mentoring and create an enabling environment to support the mentoring program. Finally, the authors recommend that a clear framework and guidelines be developed to ensure that best is attained from the practice.